2021
DOI: 10.1371/journal.pone.0248820
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing TB treatment interruption and treatment outcomes among patients in Kiambu County, 2016-2019

Abstract: Tuberculosis (TB) is the leading cause of mortality as a single infectious agent globally with increasing numbers of case notification in developing countries. This study seeks to investigate the clinical and socio-demographic factors of time to TB treatment interruption among Tuberculosis patients in Kiambu County, 2016–2019. We retrospectively analyzed data for all treatment outcomes patients obtained from TB tracing form linked with the Tuberculosis Information Basic Unit (TIBU) of patients in Kiambu County… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 11 publications
1
24
0
1
Order By: Relevance
“…About one in every ten TB patients interrupted their treatment, predominantly during intensive phase of treatment. The treatment interruption rate in our study is higher than national treatment interruption rate of 4.5% among new TB patients and 8.5% among retreatments [ 8 ] but lower compared to Kiambu county, Kenya (20.9%) [ 15 ], Ethiopia (21.21%) [ 23 ] and Mbarara hospital, Uganda (25%) [ 21 ]. This is consistent with a regional widespread problem.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…About one in every ten TB patients interrupted their treatment, predominantly during intensive phase of treatment. The treatment interruption rate in our study is higher than national treatment interruption rate of 4.5% among new TB patients and 8.5% among retreatments [ 8 ] but lower compared to Kiambu county, Kenya (20.9%) [ 15 ], Ethiopia (21.21%) [ 23 ] and Mbarara hospital, Uganda (25%) [ 21 ]. This is consistent with a regional widespread problem.…”
Section: Discussionmentioning
confidence: 67%
“…This suggests the need for continuous health education and adherence counselling. Previous studies in Kenya [ 8 , 14 , 15 ] and other Ethiopia [ 17 ] have also demonstrated higher incidences of treatment interruption during intensive phase of treatment. Nevertheless, studies in Mbarara hospital, Uganda [ 21 ] and Gondar town Ethiopia [ 25 ] indicated that interruption of TB treatment occur during continuation phase.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is likely that patients on retreatment had poor outcomes because they developed drug resistant strains as reported elsewhere [36]. Also, studies show that patient's behaviour in uences unsuccessful treatment [37,38]; a study looking at factors associated with poor outcomes indicated that patients who get lost to follow-up who then have to be retreated for TB are often reluctant to uptake and tend to interrupt treatment [20]. Studies conducted elsewhere have also shown that TB treatment exacerbates as age advances because old age comes with increased age-related immunosuppressant comorbidities such as diabetes mellitus that increase adverse effects of anti-TB drugs, cause drug resistance, mortality, and increases recurrence of TB in this group [28,39,40].…”
Section: Discussionmentioning
confidence: 92%
“…Kenya is listed among the top 30 TB high burdened countries [7]. Kenya is also among 14 countries globally that suffer from the TB, TB-HIV co-infection, and Multi-Drug Resistant TB [8] triple burden. The TB prevalence for Kenya in 2015 was 233 per 100,000 population with a mortality of 20 per 100,000.…”
Section: Introductionmentioning
confidence: 99%